Praising the blade as a genre of «magtal» in the poetry of A. Suseev, D. Kugultinov and M. Khoninov - R. M. Khaninova (Nomadic Civilization: Historical Research, 2022)
The article examines the genre of magtal in the aspect of the greatness of bladed weapons on the examples of magtal poems in the poetry of Aksen Suseev, David Kugultinov and Mikhail Honinov. If “Uldin magtal” (“The Greatness of the Sword”) is included in A. Suseev’s poem “Teegin urn” (“Son of the Steppes”, 1939) as part of three magtals addressed to the greatness of the hero, horse and his weapons, before 12 songs-chapters, then D. Kugultinov’s poems “Aakun shor-uld taig” (“The sword-cane of Oka”, 1956) and M. Honinov’s “Khazg Chashkin ir ...” (“The blade of the Cossack saber ...”) are separate magtals dedicated to the heroes of fellow countrymen. A. Suseev and D. Kugultinov have magtals addressed to the hero of the Civil War O.I. Gorodovikov, M. Honinov — the hero of the Patriotic War B.B. Gorodovikov, defenders of the Fatherland. Comparative-typological analysis of folklore analogues in the epic “Dzhangar” and literary magtals revealed both common and different in the glorification of the hero through the glorification of his weapons — sword, saber, Cossack saber.